Australian General lnsurance: Paradigm shift in Distribution Model - Kumar, Shishir (Assurances et gestion des risques / Insurance and Risk Management, 2009)
Australian General insurance industry has witnessed historically strong profit. And, the profitability is expected to be strong in the years to come, as a result of continuous low enforcement and changing market dynamics. However, the industry is witnessing structural changes over the years. Government’s regulatory mechanisms to protect industry and investors are pushing small players towards consolidation. The intensified competition has also led to decline in the number of insurers and clustering amongst the local brokers. Brokers are expected to gain in the personal as well as commercial line of business in near term. Brokers’ gain in personal lines seems to be surprising.